Kirkeminister Vilhelm Fibiger - Malmgart, Liselotte (Kirkehistoriske Samlinger, 1997)
Vilhelm Fibiger (1886-1978) was a conservative politician, closely connected to the politician John Christmas Møller and personally connected to Indre Mission, an evangelical movement in the Church of Denmark. In this speech, delivered in 1961, Fibiger describes his experiences as a member of the Danish government during the Second World War, particularly his time as a Minister of Ecclesiastical Affairs 1940-42. Among other things Fibiger describes his meetings with Kaj Munk (Danish vicar, killed by Germans) and the time he spent in September of 1943 in Horserød, a prison camp in North Zealand.